Linguistic validation of the simplified Chinese version of the US National Cancer Institute’s patient-reported outcomes version of the common terminology criteria for adverse events (PRO-CTCAE™) - Kkf, C. (BioMed Central Ltd, 2021)
10.1186/s12885-020-07631-5